Analisis Kritis Penetapan Tersangka Dokter Spesialis On Call dalam Dugaan Malpraktik - Emirza Nur Nur Wicaksono (Jurnal JURISTIC, 2026)
This study aims to analyze the legal framework for naming specialist doctors as suspects in alleged malpractice cases stemming from on-call medical consultations. It examines the fulfillment of the elements of criminal liability and medical professional standards, and formulates a legal policy framework to prevent the overcriminalization of medical practice. The study employed normative legal methods with statutory, conceptual, and case-based approaches. Legal materials were obtained through a literature review of relevant laws and regulations, legal doctrine, court decisions, and scientific literature. The analysis was conducted qualitatively through legal interpretation and juridical argumentation. The results indicate that specialist doctors providing on-call consultations cannot automatically be held criminally liable simply because harm occurs to patients. Criminal liability must be based on proof of a deviation from professional standards, justifiable error, and a clear causal relationship between the doctor's actions and the resulting consequences. This study also identified the potential for overcriminalization due to the overly broad use of criminal law in resolving medical disputes. Therefore, regulatory reform, strengthening of independent medical audit mechanisms, and affirmation of the principle of ultimum remedium are needed to ensure a balance between patient protection and legal protection for medical personnel.